2022
DOI: 10.3390/cancers14163890
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Splice Variant of BCAS1 Inhibits β-Arrestin 2 to Promote the Proliferation and Migration of Glioblastoma Cells, and This Effect Was Blocked by Maackiain

Abstract: Brain-enriched myelin-associated protein 1 (BCAS1) is frequently highly expressed in human cancer, but its detailed function is unclear. Here, we identified a novel splice variant of the BCAS1 gene in glioblastoma multiforme (GBM) named BCAS1-SV1. The expression of BCAS1-SV1 was weak in heathy brain cells but high in GBM cell lines. The overexpression of BCAS1-SV1 significantly increased the proliferation and migration of GBM cells, whereas the RNA-interference-mediated knockdown of BCAS1-SV1 reduced prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…In this case report, a compact cluster of BCAS1 + cells was described for the first time in a glioma [15]. Finally, a novel splice variant of BCAS1 has been linked with high proliferation and migration rate of the glioblastoma [16]. Given all the evidence showing that this OPC marker might play an important role in gliomagenesis, in this study, we analyzed the expression of BCAS1 in a cohort of 85 samples from patients diagnosed with diffuse gliomas, including OG, AS and GB.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…In this case report, a compact cluster of BCAS1 + cells was described for the first time in a glioma [15]. Finally, a novel splice variant of BCAS1 has been linked with high proliferation and migration rate of the glioblastoma [16]. Given all the evidence showing that this OPC marker might play an important role in gliomagenesis, in this study, we analyzed the expression of BCAS1 in a cohort of 85 samples from patients diagnosed with diffuse gliomas, including OG, AS and GB.…”
Section: Introductionmentioning
confidence: 68%
“…The fact of having detected more grade 3 OG samples with BCAS1 + nodules, increase the interest of further elucidate the function of BCAS1 + cell population in those tumors. BCAS1 upregulation has been recently associated with migration, proliferation and recurrence in GB [16,45]. Finally, although the expression of BCAS1 has been associated with prognosis in different cancers, including prostate [11], pancreatic [12], colorectal [13] and gastric cancer [14], more studies are needed to fully understand how BCAS1 expression affects the function of neoplastic cells in diffuse gliomas, including its role in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The similar rise in the U87‐MG cell line led us to conduct additional research. Previous studies have suggested that glial cells may demonstrate the expression of both α‐synuclein and β‐Arrestin 2, especially under certain conditions 32,33 . Elevated levels of p‐MEK‐2 in GBM indicate a potential involvement in chemoresistance, which adds complexity to its utility as a specific marker 34 …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that glial cells may demonstrate the expression of both α-synuclein and β-Arrestin 2, especially under certain conditions. 32,33 Elevated levels of p-MEK-2 in GBM indicate a potential involvement in chemoresistance, which adds complexity to its utility as a specific marker. 34 Our research hints that morphine may influence these markers through mechanisms that are not limited…”
Section: Evaluation Of Neuroadaptation Development Markers In Morphin...mentioning
confidence: 99%